Boii – Taurisci - Karwowski, Maciej; Ramsl, Peter C. (2016)
This volume is the result of a conference, which was held from June 14–15, 2012 at the Event Centre Schüttkasten in Klement-Oberleis, Lower Austria. The thematic focus of the contributions was the nature of contacts and relations between the settlement areas of the La Tène culture, which are associated with the Celtic tribes of the Boii and Taurisci on the basis of numismatic and written sources. The paradigm shifts in Iron Age archaeology and the veritable explosion of new archaeological materials and find contexts (coins, fibulae, Knotenringe, architecture and settlement features) have found their expression in this volume. Dieser Band ist das Ergebnis einer Konferenz, welche vom 14.−15. Juni 2012 im Veranstaltungszentrum Schüttkasten in Klement-Oberleis, Niederösterreich stattfand. Den thematischen Schwerpunkt der Beiträge bildete der Verlauf der Hauptkontakte und Beziehungen zwischen den Siedlungsgebieten der Latènekultur, die aufgrund der numismatischen und schriftlichen Quellen mit den keltischen Stämmen der Boier und Taurisker in Verbindung gebracht werden. Eingang in den Band fand die Darstellung der Paradigmenwechsel und die wahrhaftige Explosion von neuen Fund- und Befundkategorien (Münzen, Fibeln, Knotenringe, Architektur und Siedlungsbefunde).